Secret Key Identification of BC3, AES, and DES Encryption Devices using Power Analysis Attacking Technique - YUDHIPRAWIRA - Nim: 18213024 , MARIO
Cryptography is a science of creating a secret message and it is constantly developed. The development said consists of attacking and defending the cryptography itself. Power analysis is one of many Side-Channel Analysis (SCA) attack technique. Power analysis is an attacking technique that uses the information of a cryptographic hardwareÃ‚Â’s power consumption. Power analysis is carried on by utilising a side-channel information to a vulnerability in a cryptography algorithm. Power analysis also uses a mathematical model to recover the secret key of the cryptographic device. This research uses design research methodology as a research framework started from research clarification to descrtptive study. In this research, power analysis attack is implemented to three symmetrical cryptography algorithms: DES (Data Encryption Standard), AES (Advanced Encryption Standard), and BC3 (Block Cipher 3). The said attack has successfully recovered 100% of AES secret key by using 500 traces and 75% DES secret key by using 320 traces. The research concludes that power analysis attack using Pearson Correlation Coefficient (PCC) method produces more optimal result compared to difference of means method.